Follow-up study of improved cookstoves in the Cuzco region of Peru. Issue 1 (2nd January 2017) - Keese, James; Camacho, Alejandra; Chavez, Aurora
ABSTRACT: Approximately three billion people use traditional biomass cookstoves. These stoves contribute to indoor air pollution, notably affecting women and children, and to deforestation and climate change. Improved cookstoves have been offered as a solution, but low rates of adoption are common among stove programmes. This paper is a follow-up study of a stove programme run by the NGO Proworld Service Corps in Cuzco, Peru. A survey was administered in 43 households in three communities. The results indicate an adoption rate of 70% and identify the characteristics of the stoves that contribute to their adoption and sustained use.